Iron (II) Removal Using Activated Silica/Lignin Composite: Kinetic and Equilibrium Studies - Atiek Rostika Noviyanti; Yati B Yuliyati; Ghaissani Nur Maulani; Irwan Kurnia (Syarif Hidayatullah State Islamic University, 2022)
Recently, the Indonesian industry has been rapidly developed and affects the number of heavy metal ions waste such as iron (II). Iron (II) is dangerous to the environment because it is harmful to aquatic systems and carcinogenic. This research used activated silica/lignin to remove iron (II) in water. The activated silica/lignin was isolated from rice husk and activated by sodium periodate with a 10% weight of lignin in the range of pH of 2–5 at 55 °C. Then its specific surface area was analyzed with the methylene blue adsorption method. It is found that the condition in pH 2 showed the best isolation and activation condition to achieve the lowest impurity (cellulose and hemicellulose) in silica/lignin composite. Furthermore, the activated silica/lignin composite, isolated in pH 2, has a specific surface area of 366.6372 m2/g with the highest adsorption value of 1.1825 mg g-1 for iron (II) ions solution (5 ppm) within a contact time of 90 minutes. Moreover, the adsorption kinetics followed the pseudo-second-order kinetic model, also the adsorption isotherm fitted with the Freundlich model. This research showed that activated silica/lignin could be used as an alternative of environmentally friendly material for iron (II) removal in water.